2013
DOI: 10.1038/ncomms2742
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 regulates differentiation of brown and beige adipocytes via a bistable circuit

Abstract: Brown adipocytes are a primary site of energy expenditure and reside not only in classical brown adipose tissue but can also be found in white adipose tissue. Here we show that microRNA 155 is enriched in brown adipose tissue and is highly expressed in proliferating brown preadipocytes but declines after induction of differentiation. Interestingly, microRNA 155 and its target, the adipogenic transcription factor CCAAT/enhancer-binding protein β, form a bistable feedback loop integrating hormonal signals that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
199
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(205 citation statements)
references
References 58 publications
5
199
1
Order By: Relevance
“…Previous studies reported that TGF-β-mediated Smad4 expression induces miR-155 promoter activity and enriches miR-155 expression to contribute to cell migration and invasion (38), and found that NF-κB, STAT5, or CCAAT/enhancer binding protein beta (C/EBPβ) could bind to miR-155 promoter region and induce miR-155 expression in colon cancer, cutaneous T-cell lymphoma, or fat cells (20,39,40). miR-155 has been considered an "oncomicroRNA" by targeting several tumor suppressors, including SOCS1, FOXO3a, RhoA, C/EBPβ, PP2A/C, and von Hippel-Lindau tumor suppressor (VHL), and it has been found to promote the EMT, invasion, metastasis, growth, and angiogenesis of cancer cells (20,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that TGF-β-mediated Smad4 expression induces miR-155 promoter activity and enriches miR-155 expression to contribute to cell migration and invasion (38), and found that NF-κB, STAT5, or CCAAT/enhancer binding protein beta (C/EBPβ) could bind to miR-155 promoter region and induce miR-155 expression in colon cancer, cutaneous T-cell lymphoma, or fat cells (20,39,40). miR-155 has been considered an "oncomicroRNA" by targeting several tumor suppressors, including SOCS1, FOXO3a, RhoA, C/EBPβ, PP2A/C, and von Hippel-Lindau tumor suppressor (VHL), and it has been found to promote the EMT, invasion, metastasis, growth, and angiogenesis of cancer cells (20,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…The brown transcriptional program could be corroborated by miR-378 that increases cAMP production via targeted degradation of phosphodiesterase 1B (Pde1b) (12) or by miR-30b that promotes degradation of Rip140, a transcriptional corepressor (13). Conversely, decreased levels of miR-133, miR-27a, miR-106b/93, and miR-155 have shown to enhance brown adipogenesis by preventing targeted degradation of transcription factors of Prdm16 (14), Ppar␥ (15), Ppar␣ (16), and C/ebp␤ (17), respectively (see Fig. 1E).…”
mentioning
confidence: 99%
“…In our opinion it will be important in the future to study factors which inhibit BAT activity with the same attention given to those that promote its activity. Our work, in fact, is one of a few 46,47 that focuses on an endogenous player that impairs BAT formation and activity. Only such an extended approach will allow us to draw a more comprehensive picture of the molecular mechanisms that regulate BAT activity to design new interventions that would take advantage of its potential to ameliorate metabolic diseases.…”
mentioning
confidence: 99%